Registration of three new bmr12 sorghum mutants from an ethyl methane sulfonate–induced BTx623 mutant population. Issue 2 (9th April 2022) - Emendack, Yves; Xin, Zhanguo; Hayes, Chad; Burow, Gloria; Sattler, Scott; Bean, Scott; Smolensky, Dmitriy
Abstract: Three new sorghum ( Sorghum bicolor L.) brown midrib ( bmr ) genetic stocks BTx623 bmr12‐30 (Reg. no. GS‐790, PI 699404), BTx623 bmr12‐34 (Reg. no. GS‐789, PI 699405), and BTx623 bmr12‐35 (Reg. no. GS‐788, PI 699406) were developed for release by USDA–ARS in Lubbock, TX. The primary purpose for the release of these stocks is to provide an extensive source of ( bmr12 ) variants for use in forage breeding programs. The genetic stocks were isolated from the pedigreed sorghum ethyl methane sulfonate–mutagenized sorghum in BTx623 background. The derived mutations were analyzed by DNA sequencing and confirmed by KASP (Kompetitive Allele Specific PCR) markers. The confirmed bmr mutants were also analyzed for stem and leaf lignin and carbohydrate contents. Furthermore, physiological and agro‐morphological evaluations were performed under control and field conditions. All genetic stocks displayed the reddish‐brown pigmentation in the leaf midrib, confirming the bmr phenotype. The bmr12 mutants flowered 4–5 d earlier than the wild type BTx623. Physical and compositional characterization of seeds from the three genetic stocks revealed no negative consequence of bmr on grain structure. Notably, these bmr12 mutants had 14–24% greater total seed protein than wild type BTx623. The three new bmr12 alleles provide public and private breeders crucial and novel genetic stock sources for use in breeding bmr forage sorghum. Core Ideas: Three new bmr12 genetic stocks from EMS‐induced BTx623 were confirmed by KASP markers. The three new bmr12 alleles provide public and private breeders crucial and novel genetic stock. All genetic stocks displayed the reddish‐brown pigmentation in the leaf midrib, confirming the bmr phenotype. The bmr12 mutants flowered 4‐5 d earlier than the wild type. Mutants had a 14‐24% greater total seed protein than BTx623 wild type.